The contribution of corporate social responsibility perception on job performance: does corporate reputation matter? - Vuong, Bui Nhat; Tung, Dao Duy; Huan, Dao Duy (Business: Theory and Practice, 2022)
The objective of this study is to examine the relationship between corporate social responsibility (CSR) and job performance through the mediating role of job attitudes. In addition, the moderating role of organizational reputation is also considered. Based on stakeholder theories, signaling theory, social exchange theory, and social identity theory, a research model has been developed. Data has been collected from 636 employees working in SMEs in Vietnam to provide empirical evidence. Research results showed that corporate social responsibility has made a positive contribution to improving job performance and this relationship was partially mediated by job attitudes. In addition, organizational reputation strengthened the positive connection between CSR and job attitudes. Finally, the study suggested some managerial implications to help leaders have appropriate policies to improve employees’ job performance.